Relative age effects and academic timing in Canadian interuniversity football. (2nd January 2018) - Chittle, Laura; Horton, Sean; Dixon, Jess C.
ABSTRACT: Relative age effects (RAEs) explain the (dis)advantages individuals experience as a result of when they are born relative to a pre-determined cut-off date. Within an interuniversity setting, academic timing (AT) may moderate the RAE pattern due to some student-athletes having eligibility years that do not correspond with their birth years. The purpose of this study was to examine the influence of the RAE and AT on interuniversity football players. A series of chi-square goodness of fit tests ( χ 2 ) revealed no RAE when all student-athletes were analyzed together as well as among those who were delayed (i.e. eligibility years that correspond with a younger cohort), and a traditional RAE among those who were on-time (i.e. eligibility years that correspond with their year of birth). Student-athletes ranged between 1 and 12 years delayed, with the majority of these athletes being delayed by one (30.76%) or two years (30.97%). This study suggests that there may be advantages to student-athletes delaying their participation within football, as these delays may help mitigate the overall RAE by equalizing playing opportunities for relatively younger student-athletes. However, delaying eligibility raises concerns about equity, particularly for those progressing to interuniversity football directly out of high school who may have to compete for roster spots against student-athletes who may be up to 12 years delayed.